Realisasi Kerjasama Badan Usaha PT. Pelabuhan Kepulauan Riau Dengan PT. Nusantara Maha Karya Membangun Pelabuhan Pengumapan di Batam: Perspektif Collaborative Governance - Wahyu Deka Ananta; Ashar Ashar; Januarman Januarman (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2022)
Cooperation of PT. Tanjung Pinang Port with PT. Nusantara Maha Karya is motivated by the government’s desire to build quality facilities and infrastructure that can be used according to standards so that shipping centers located in Riau Islands can be fully touched by Riau Islands so that equitable distribution of infrastructure, especially ports in Riau Islands, can invite investors to invest in this port so that it can become a source of income. Beneficial for the Riau Islands community, especially in accordance with the autonomy law in regional development. To measure the effectiveness of researchers divided into 3 levels. First, it is only limited to the implementation or operationalization of the program. Second, implementing the program and delivering results in accordance with the objectives in the MoU Agreement. Third, program implementation. By using the level of domestic analysis, interaction theory and several concepts of cooperation, PT. Tanjung Pinang Port with PT. Nusantara Maha Karya, the argument will be proven that the cooperation in the development of the feeder port in Batam is only limited to program implementation, while the cooperation with PT. Tanjung Pinang Port with PT. Nusantara Maha Karya arrived at the implementation and provided results for the Riau Islands community in accordance with the objectives in the MoU Agreement. At the end of this study, by using the level of analysis, theory and concept, which were analyzed based on development programs and activities with the perspective of Collaborative Governance that took place, it turned out to produce an answer that the cooperation of PT. Tanjung Pinang Port with PT. Nusantara Maha Karya is only limited to the implementation of the feeder port development program to the implementation to provide results for the Riau Islands community in accordance with the objectives in the MoU Agreement.